Mindfulness at psychological ill-being: relationship between the acceptance of internal experience and anxiety in undergraduate students - Alberto Paramio Leiva; Daniel Cruz Jurado; Antonio Zayas García; Paloma Gil-Olarte Márquez; Rocío Guil Bozal (INFAD, 2018)
The high prevalence and incidence of problems related to anxiety in the population have made it one of the main indicators of psychological ill-being (Guillén-Riquelme Buela-Casal, 2011). Numerous researchers are studying its treatment by the use of therapeutic techniques of third generation based on mindfulness because it has become a practice of ascending use in the clinical exercise and the development of psychological health (Ford, Lam, John, Mauss, 2017). The evidences in this regard show that there could be a tendency to publish only those investigations that report positive effects, which could be causing an exaggeration of reality (Coronado-Montoya et al., 2016). The present research has two objectives: (1) know the statistical relationship between the factors of Mindfulness (Observation, Description, Acting with awarenesse, Non-judging, and Non-reactivity) and anxiety (state and trait); and (2) check the explanatory capacity of these factors on both types of anxiety. A sample of 53 undergraduated students (third and fourth degree) from the University of Cádiz was used. They voluntarily completed the following questionnaires: Five Facet Mindfulness Questionnaire (Aguado et al., 2015) and State Trait Anxiety Inventory (Buela-Casal, GuillénRiquelme, Seidedos, 2011). The bivariate correlation analysis performed showed that only the Non judging, Acting with awareness and Non-reactivity factors, correlated negatively and statistically significant with both types of anxiety. These factors were able to explain the change in the variance of state anxiety in 57.8% (R2 = .578), and in 62.7% in trait anxiety (R2 = .627). The factors Non judging (Beta = -.508) and Acting with awareness (Beta = -.346), were statistically significant when explaining levels of trait anxiety. However, only Non judging (Beta = -.693) remained as significant factor in anxiety state. In conclusion, the promotion of accepting nonevaluative attitude before the internal experience would seek an improvement in the levels of both types of anxiety and, in addition, paying full attention to the activities during its realization would suppose a decrease in the trait anxiety